Time-varying double-peaked emission lines following the sudden ignition of the dormant galactic nucleus AT2017bcc - Ridley, E.J.; Nicholl, M.; Ward, C.A.; Blanchard, P.K.; Chornock, R.; Fraser, M.; Gomez, S.; Mattila, S.; Oates, S.R.; Pratten, G.; Runnoe, J.C.; Schmidt, P.; et al. (Oxford University Press, 2025)
We present a pan-chromatic study of AT2017bcc, a nuclear transient that was discovered in 2017 within the skymap of a reported burst-like gravitational-wave candidate, G274296. It was initially classified as a superluminous supernova, and then reclassified as a candidate tidal disruption event. Its optical light curve has since shown ongoing variability with a structure function consistent with that of an active galactic nucleus, however, earlier data show no variability for at least 10 yr prior to the outburst in 2017. The spectrum shows complex profiles in the broad Balmer lines: a central component with a broad-blue wing, and a boxy component with time-variable blue and red shoulders. The H α emission profile is well modelled using a circular accretion disc component, and a blue-shifted double Gaussian which may indicate a partially obscured outflow. Weak narrow lines, together with the previously flat light curve, suggest that this object represents a dormant galactic nucleus which has recently been re-activated. Our time-series modelling of the Balmer lines suggests that this is connected to a disturbance in the disc morphology, and we speculate this could involve a sudden violent event such as a tidal disruption event involving the central supermassive black hole, though this cannot be confirmed, and given an estimated black hole mass of ≿ 107–108 M☉ instabilities in an existing disc may be more likely. Although we find that the redshifts of AT2017bcc (z = 0.13) and G274296 (z > 0.42) are inconsistent, this event adds to the growing diversity of both nuclear transients and multimessenger contaminants. © 2024 The Author(s).